Important questions for Class 9 Maths Chapter 2 Polynomials are provided here to help the CBSE students score well in their Class 9 Maths exam. The practice questions given here from polynomials chapter (NCERT) will help the students to create a better understanding of the concepts and thus, develop their problem-solving skills.

**Also Check:**

- Important 2 Marks Questions for CBSE 9th Maths
- Important 3 Marks Questions for CBSE 9th Maths
- Important 4 Marks Questions for CBSE 9th Maths

## Important Polynomials Questions For Class 9- Chapter 2 (With Solutions)

Some important questions from polynomials are given below with solutions. These questions will help the 9th class students to get acquainted with a wide-variation of questions and develop the confidence to solve polynomial questions more efficiently.

**1. Give an example of a monomial and a binomial having degrees as 82 and 99, respectively.**

**Solution:**

An example of monomial having a degree of 82 = x^{82}

An example of a binomial having a degree of 99 = x^{99Â }+ x

**2.Â Compute the value of 9x ^{2} + 4y^{2} if xy = 6 and 3x + 2y = 12.**

**Solution:**

Consider the equation 3x + 2y = 12

Now, square both sides:

(3x + 2y)^{2} = 12^{2}

=> 9x^{2} + 12xy + 4y^{2} = 144

=>9x^{2} + 4y^{2} = 144 – 12xy

From the questions, xy = 6

So,

9x^{2} + 4y^{2} = 144 – 72

Thus, the value of 9x^{2} + 4y^{2 }= 72

**3.Â **Â Find the value of the polynomial 5x â€“ 4x^{2}Â + 3 at x = 2 and x = â€“1

**Solution:**

Let the polynomial be f(x) =Â 5x â€“ 4x^{2}Â + 3

Now, for x = 2,

f(2) = 5(2)Â â€“ 4(2)^{2} + 3

=> f(2) = 10 â€“ 16 + 3 = â€“3

Or,Â the value of the polynomial 5x â€“ 4x^{2}Â + 3 at x = 2 is -3.

Similarly, for x = â€“1,

f(â€“1) = 5(â€“1) – 4(â€“1)^{2} + 3

=>Â f(â€“1) =Â â€“5Â â€“4 + 3 = -6

The value of the polynomialÂ 5x â€“ 4x^{2}Â + 3 at x = -1 is -6.

**4. Calculate the perimeter of a rectangle whose area is 25x**^{2}**Â – 35x + 12.Â **

**Solution:**

Given,

Area of rectangle = 25x^{2}Â – 35x + 12

We know, area of rectangle = length Ã— breadth

So, by factoring 25x^{2}Â – 35x + 12, the length and breadth can be obtained.

25x^{2}Â – 35x + 12 = 25x^{2Â }– 15x – 20x + 12

=> 25x^{2}Â – 35x + 12 = 5x(5x – 3) – 4(5x – 3)

=> 25x^{2}Â – 35x + 12 = (5x – 3)(5x – 4)

So, the length and breadth are (5x – 3)(5x – 4).

Now, perimeter = 2(length + breadth)

So, perimeter of the rectangle = 2[(5x – 3)+(5x – 4)]

= 2(5x – 3 + 5x – 4) = 2(10x – 7) = 20x – 14

So, the perimeter = 20x – 14

**5.Â Find the value of x**^{3}**Â + y**^{3}**Â + z**^{3}**Â – 3xyz if x**^{2}**Â + y**^{2}**Â + z**^{2}**Â = 83 and x + y + z = 15**

**Solution:**

Consider the equation x + y + z = 15

From algebraic identities, we know that (a + b + c)^{2}Â = a^{2}Â + b^{2}Â + c^{2Â }+ 2(ab + bc + ca)

So,

(x + y + z)^{2}Â = x^{2Â }+ y^{2}Â + z^{2}Â + 2(xy + yz + xz)

From the question, x^{2}Â + y^{2}Â + z^{2}Â = 83 and x + y + z = 15

So,

15^{2}Â = 83 + 2(xy + yz + xz)

=> 225 – 83 = 2(xy + yz + xz)

Or, xy + yz + xz = 142/2 = 71

Using algebraic identity aÂ³ + bÂ³ + cÂ³ – 3abc = (a + b + c)(aÂ² + bÂ² + cÂ² – ab – bc – ca),

x^{3}Â + y^{3}Â + z^{3}Â – 3xyz = (x + y + z)(xÂ² + yÂ² + zÂ² – (xy + yz + xz))

Now,

x + y + z = 15, xÂ² + yÂ² + zÂ² = 83 and xy + yz + xz = 71

So, x^{3}Â + y^{3}Â + z^{3}Â – 3xyz = 15(83 – 71)

=> x^{3}Â + y^{3}Â + z^{3}Â – 3xyz = 15 Ã— 12

Or, x^{3}Â + y^{3}Â + z^{3}Â – 3xyz = 180

### More Topics Related to Class 9 Polynomials

its very nice app

tough please make the solution a bit easy

I thank byjus for providing these important questions

Nice questions but little bit difficult make it easy to solve

I don’t got question 5, step x^3+y^3+z^3-3xyz=15(83-71)

Why we subtracted 83-71??

We evaluated the value of xy + yz + xz, initially, which is equal to 71.

Since, x^3Â + y^3Â + z^3Â – 3xyz = (x + y + z)(xÂ² + yÂ² + zÂ² – (xy + yz + xz)) [By algebraic identities]

And

x + y + z = 15, xÂ² + yÂ² + zÂ² = 83 and xy + yz + xz = 71

So, if we substitute the values, we get:

x^3Â + y^3Â + z^3Â – 3xyz = 15(83 – 71)

Please go through the complete solution for the answer.

The expression is x^3+y^3+z^3 = (x+y+z)(x^2+y^2+z^2-xy-yz-xz)

= (x+y+z){(x^2+y^2+z^2)-(xy+yz+sa)}

x^2 +y^2 + z^2 = 83, xy+yz+sa = 71

This is why 83 -71 is done

This is so nice we can learn easily

wow! nice app

Thank you so much for these questions

Nice questions and its also easy to check since the solutions are given

Very helpful during online education

maths in byjus is easy.

thank you for everything